Contemporary Personnel Practices in Canadian Firms. An Empirical Evaluation - Mealiea, Laird; Lee, Dennis (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1980)
This study empirically evaluates current personnel practices in 216 Canadian firms. Specifically, 33 decision areas are considered in an attempt to determine the role of Canadian personnel departments in the organization's decision making process. Also evaluated is the possible impact of size, ownership and geographic differences on the level of involvement by personnel departments.